Construction of a co-expression network and mining of core genes for genic male sterility in sweet pepper based on transcriptome and WGCNA analysis - Meng, Yaning; Zhang, Zhe; Li, Xinxin; Zhang, Hongxiao; Yu, Zhanghong; Fan, Yanqin; Yan, Libin (Frontiers in Plant Science, 2025)
BackgroundThis study investigates the molecular mechanisms underlying genic male sterility in sweet pepper by examining the correlation between differentially expressed genes during various stages of anther development and pollen sterility.ResultsWe collected anthers from both pure fertile and sterile plants of the F2 generation of the sweet pepper genic male sterility line AB91 at three distinct developmental stages for comprehensive transcriptome sequencing. By integrating KEGG enrichment analysis with weighted gene co-expression network analysis (WGCNA), we identified Starch and sucrose metabolism (ko00500) and Phenylpropanoid biosynthesis (ko00940) as key metabolic pathways regulating genic male sterility in sweet pepper AB91. Additionally, we uncovered two specific gene modules (blue and brown) associated with genic male sterility. A total of 320 genes, which exhibited significant differences (MM≥0.8) between these two modules, were found to be highly expressed after the formation of tetrads. This finding suggests that the period following tetrad formation is a critical juncture for changes in gene expression related to genic male sterility in sweet pepper AB91. By comparing these genes with their homologs, we identified six differentially expressed genes that can serve as core genes related to genic male sterility and play essential roles during microspore development.ConclusionsThis research provides a theoretical foundation for elucidating the molecular mechanisms of genic male sterility in sweet pepper and lays the groundwork for expanding fertility gene resources and advancing hybrid breeding efforts in this important crop.